A Coronal Landmark for Tibial Component Positioning With Anatomical Alignment in Total Knee Arthroplasty: A Radiological and Clinical Study - Gong, Tianlun; Wang, Ruoyu; Gong, Song; Han, Lizhi; Yi, Yihu; Wang, Yuxiang; Xu, Weihua (Frontiers in Surgery, 2022)
Objective: The purpose of this study was to investigate the value of the lateral point of articular surface of distal tibia (LADT) for anatomical alignment in total knee arthroplasty. Methods: We reconstructed 148 three-dimensional pre-arthritic tibias and measured the tibial component inclination angle corresponding to the distal landmark of LADT. A retrospective study included 81 TKA recipients divided into the AA group and MA group. Clinical assessments including ROM, HSS, WOMAC, satisfaction for surgery, and radiological assessment were evaluated at one-year follow-up. Results: The tibial component varus angle corresponding to the distal landmark of LADT in the male and female groups were 3.38±0.33° (2.55~4.21°) and 3.16±0.31° (2.26~4.00°), respectively (p<0.05). Using LADT as the distal landmark for extramedullary tibial cutting guidance, the medial proximal tibia angle (MPTA) of the AA group was 86.99±1.15° (85.00~89.98°), and the AA and MA technique showed no difference in improvement in postoperative knee functional recovery at final follow-up. Conclusions: This study preliminarily indicated that LADT can be a reliable and economical landmark for coronal plane alignment of the tibial component.